Branchinecta orientalis Sars, 1901 (Anostraca: Branchinectidae) in Onon-Torey lakes of the Trans-Baikal Territory - Petr V. Matafonov; Natalia M. Sukhikh (Acta Biologica Sibirica)
The habitat of Branchinecta orientalis Sars, 1901 in the Onon-Torey lakes of the Trans-Baikal Territory (Russia) was established according to the results of molecular-phylogenetic analysis of individuals from Lakes Bain-Tsagan and Nozhiy. Mitochondrial 12SrRNA and CO1 sequences from Transbaikalia were integrated into the pool of Asian populations of B. orientalis. Both studied CO1 haplotypes turned out to be individual, although at a distance of two or three nucleotide substitutions from one of the most numerous Mongolian-Tibetan haplotypes. Materials on the morphology and abundance of B. orientalis in the lakes of Bain-Tsagan, Nozhiy and Tsagan-Nur are presented. The similarity of the basal segment of the second antennae of B. orientalis Sars male from Onontorean lakes and Branchinecta minuta was revealed. The authors substantiate the fallacy of previous indications of Artemia salina in the group of Torey lakes and the attribution of data on the abundance and functional indicators of this species for the 1980s.